Cardiac power output ratio: Novel survival predictor after percutaneous ventricular assist device in cardiogenic shock - Calvin Leung; Ivan Man Ho Wong; Cheuk Bong Ho; Michael Chi Shing Chiang; Yan Hang Fong; Pok Him Lee; Tai Chung So; Yin Kei Yeung; Chung Yin Leung; Yuet Wong Cheng; Shing Fung Chui; Alan Ka Chun Chan; et al. (ESC Heart Failure)
Abstract Aims Currently, there is limited data on prognostic indicators after insertion of percutaneous ventricular assist device (PVAD) in the treatment of cardiogenic shock (CS). This study evaluated the prognostic role of cardiac power output (CPO) ratio, defined as CPO at 24 h divided by early CPO (30 min to 2 h), in CS patients after PVAD. Methods and results Consecutive CS patients from the QEH‐PVAD Registry were followed up for survival at 90 days after PVAD. Among 121 consecutive patients, 98 underwent right heart catheterization after PVAD, with CPO ratio available in 68 patients. The CPO ratio and 24‐h CPO, but not the early CPO post PVAD, were significantly associated with 90‐day survival, with corresponding area under curve in ROC analysis of 0.816, 0.740, and 0.469, respectively. In multivariate analysis, only the CPO ratio and lactate level at 24 h remained as independent survival predictors. The CPO ratio was not associated with age, sex, and body size. Patients with lower CPO ratio had significantly lower coronary perfusion pressure, worse right heart indices, and higher pulmonary vascular resistance. A lower CPO ratio was also significantly associated with mechanical ventilation and higher creatine kinase levels in myocardial infarction patients. Conclusion In post‐PVAD patients, the CPO ratio outperformed the absolute CPO values and other haemodynamic metrics in predicting survival at 90 days. Such a proportional change of CPO over time, likely reflecting native heart function recovery, may help to guide management of CS patients post‐PVAD.